Validation of ammonia diffusive and pumped samplers in a controlled atmosphere test facility using traceable Primary Standard Gas Mixtures. (15th February 2019) - Martin, Nicholas A.; Ferracci, Valerio; Cassidy, Nathan; Hook, Josh; Battersby, Ross M.; di Meane, Elena Amico; Tang, Yuk S.; Stephens, Amy C.M.; Leeson, Sarah R.; Jones, Matthew R.; Braban, Christine F.; Gates, Linda; et al.
Abstract: We report the determination of ammonia (NH3 ) diffusive sampling rates for six different designs of commercial diffusive samplers (CEH ALPHA sampler, Gradko diffusion tube, Gradko DIFRAM-400, Passam ammonia sampler, and ICS Maugeri Radiello radial sampler (blue and white turbulence barriers)), together with the validation test results for a pumped sampler (CEH DELTA denuder). The devices were all exposed in the UK's National Physical Laboratory's (NPL) controlled atmosphere test facility (CATFAC). For each of the seven diffusive sampler exposure tests there were traceable concentrations of ammonia (in the range 3–25 μg m −3 ) generated under well-defined conditions of temperature, relative humidity and wind speed, which are applicable to a variety of ambient monitoring environments. The sampler exposure time at each concentration was 28 days, except for the radial devices, which were exposed for 14 days. The work relied on the dilution of newly developed stable Primary Standard Gas Mixtures (PSMs) prepared by gravimetry in passivated gas cylinders as a method of improving the metrological traceability of ammonia measurements. The exposed diffusive samplers were sent blind to the participants for analysis and the reported NH3 concentrations were then compared against the known reference concentration. From the results for each sampler type a diffusive sampling rate was calculated and compared against the rate used routinely by the participants. Some measurement results were in good agreement with the known traceable reference concentration (particularly for one diffusive sampler design (ALPHA)), while other devices exhibited over-reading and under-reading (each with a clear bias). The new diffusive sampling rates determined in the laboratory study were then applied to measurements in a field comparison campaign, and this was found to deliver an improvement in agreement between the different devices deployed. Highlights: Development of Primary Standard Gas Mixtures of ammonia prepared by gravimetry. Exposure of pumped and diffusive samplers in a controlled atmosphere test facility. New ammonia diffusive sampling rates for wide range of commercial samplers. Improved traceability and accuracy of ambient measurements of ammonia in the field.